Are Neighbourhood Walkability and Greenness Associated with Increased Physical Activity and Better Self-Rated Health? Findings from the Beyond Health Survey of Adults in Ottawa, Canada. (June 2017) - Villeneuve, Paul; Root, Ariel; Kumar, Neerija; Ambrose, Sarah; DiMuzio, Jason; Rainham, Daniel; Ysseldyk, Renate
Abstract : Background: Several studies have found that features of the built environment, such as walkability and greenness, are associated with physical activity and health. However, few have evaluated seasonal differences, or been able to discriminate between physical activities performed within versus outside individuals' neighborhoods. Methods: This was a cross-sectional study that collected data from 308 Ottawa adult residents using an online survey (BEYOND-Health; The Built Environment: Your Ottawa Neighbourhood and Determinants of Health) administered between January and March, 2016. Individuals provided information on their participation in physical activity both overall, as well as those performed within their neighborhoods during the summer and winter. They also provided information on a number of socio-demographic characteristics, and their physical and mental health. Place of residence was captured using postal codes. Neighbourhood walkability was determined using the Walk Score®, while the Normalized Difference Vegetation Index (NDVI) was used to describe the availability of vegetation at their place of residence. Logistic regression was used to determine the relationship between both Walk Score® and NDVI with physical activity. Least squares adjusted means for age and sex were used to examine the relationship between physical activity in neighbourhood (hours per week) and Walk Score ®, as well as NDVI, by season. Results: Neighborhood walkability was positively associated with participants' age, and inversely associated with income. No clear gradient with these factors was evident for the NDVI. Overall there was no association between the hours of physical activity and neighborhood walkability in either the winter (p=0.59) or summer (p=0.68). However, when analyses were restricted to activities performed within their neighborhoods, those who lived in more walkable neighborhoods were more physically active during the winter season. Specifically, those in the upper quartile of walkable neighborhoods participated in 5.4 hours weekly of physical activity compared to 3.6 hours in the lowest quartile (p<0.01). Walkability was also related to overall self-rated health as those individuals of 'excellent' health had a mean Walk Score® of 68.6, whereas those with 'poor' health had a mean 55.6 (p<0.01). No associations between greenness and physical activity were observed in any model. Conclusions: Our findings suggest that walkability, rather than greenness, is a more important predictor of participation in physical activity and overall health. In addition, for studies that aim to better understand the impacts of the urban built environment on physical activity, our findings highlight the relevance of characterizing physical activity behaviors by season and location.